Nonspecific Binding Domains in Lipid Membranes Induced by Phospholipase A2 - Hong, Chia Yee (Langmuir : the ACS journal of surfaces and colloids, 2016)
Phospholipase A2 (PLA2) is a peripheral membrane protein that can hydrolyze phospholipids to produce lysolipids and fatty acids. It has been found to play crucial roles in various cellular processes and is thought as a potential candidate for triggering drug release from liposomes for medical treatment. Here, we directly observed that PLA2 hydrolysis reaction can induce the formation of PLA2-binding domains at lipid bilayer interface and found that the formation was significantly influenced by the fluidity of the lipid bilayer. We prepared supported lipid bilayers (SLBs) with various molar ratios of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) to adjust the reactivity and fluidity of the lipid bilayers. A significant amount of the PLA2-induced domains was observed in mixtures of DPPC and DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine) but not in either pure DPPC or pure DOPC bilayer, which might be the reason that previous studies rarely observed these domains in lipid bilayer systems. The fluorescently labeled PLA2 experiment showed that newly formed domains acted as binding templates for PLA2. The AFM result showed that the induced domain has stepwise plateau structure, suggesting that PLA2 hydrolysis products may align as bilayers and accumulate layer by layer on the support, and the hydrophobic acyl chains at the side of the layer structure may be exposed to the outside aqueous environment. The introduced hydrophobic region could have hydrophobic interactions with proteins and therefore can attract the binding of not only PLA2 but also other types of proteins such as proteoglycans and streptavidin. The results suggest that the formation of PLA2-induced domains may convert part of a zwitterionic nonsticky lipid membrane to a site where biomolecules can nonspecifically bind